BROMOPROPANE; A REVIEW ARTICLE - Noor M. Mohammed; Ahmed M. Al-Yassen (Scholar Express Journals, 2022)
Bromopropane (BP) was introduced into the workplace as an alternative to ozone depleting solvents and increasingly used in manufacturing industry, bromopropane can be absorbed by inhalation, ingestion, or dermal exposure. Several studies have monitored urine and blood samples in workers to establish biomarkers of exposure. 1-bromopropane metabolism show that CYP catalyzed oxidation (primarily via CYP2E1) reactions and glutathione conjugation are the primary metabolic pathways. Bromopropane has many reactive intermediate metabolites (bromoacetone, glycidol, and - bromohydrin). Workers that exposed to BP showed different systems toxicities, animal studies showed toxicities as well. BP cause disruption of estrous cycle and change ovarian shape and weight, there is a general agreement that male reproductive organs are particularly susceptible to the deleterious effects of reactive oxygen species (ROS) and lipid peroxidation, which ultimately lead to impaired fertility. Human cases of BP toxicity showed ataxia, sensory deficit and hyperreflexia in lower extremities. The reduction of hepatic GSH produced by BP was associated with increased activities of alanine aminotransferase (ALT) and aspartate aminotransferase (AST). Other toxicities further reported like reduction in mean body weight of rats, pancytopenia and bone marrow hypoplasia.
Keywords: reported; hepatic; fertility; reproductive